2016
DOI: 10.1002/col.22094
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of a spectrally tunable LED daylight simulator

Abstract: Daylight simulators (i.e., D50, D55, D65, and D75 simulators) play an important role for industrial applications, such as surface color industry, recipe formulation, and graphic arts industry. Conventional light sources, including xenon lamps, tungsten‐halogen lamps, and fluorescent lamps, have been used as daylight simulators. In this article, a genetic algorithm is employed to investigate optimized channels for each daylight simulator. It is found that at least six LED channels are required to produce high q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…13 Recently, it was reported that at least six LED channels with full widths at half maximum (FWHM) of 30 nm were required to produce AA-grade daylight simulators. 16 However, we found that FWHMs of LEDs used in the six channels reported by Wei were 50 nm, not 30 nm (which is an average value of AlInGaP and AlGaInN LEDs). 17 Therefore, it is impossible to implement AA-grade daylight simulators with six single-color LED channels.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…13 Recently, it was reported that at least six LED channels with full widths at half maximum (FWHM) of 30 nm were required to produce AA-grade daylight simulators. 16 However, we found that FWHMs of LEDs used in the six channels reported by Wei were 50 nm, not 30 nm (which is an average value of AlInGaP and AlGaInN LEDs). 17 Therefore, it is impossible to implement AA-grade daylight simulators with six single-color LED channels.…”
Section: Introductionmentioning
confidence: 64%
“…In addition, there were significant differences between the colorimetric performances (such as chromaticity, color rendition, and CIE metamerism) of the daylight simulator and that of the standard daylight illuminant . Recently, it was reported that at least six LED channels with full widths at half maximum (FWHM) of 30 nm were required to produce AA‐grade daylight simulators . However, we found that FWHMs of LEDs used in the six channels reported by Wei were 50 nm, not 30 nm (which is an average value of AlInGaP and AlGaInN LEDs) .…”
Section: Introductionmentioning
confidence: 99%
“…The quality of a daylight simulator in simulating Commission Internationale de l'Eclairage (CIE) daylight illuminant can be evaluated by comparing the appearance of a set of color samples which includes the visible range metamerism index ( M v ) and the ultraviolet‐range metamerism index ( M u ) for evaluating D50, D55, D65, and D75 simulators, where M v is the average of the color differences between the five virtual metameric pairs of color samples under a simulator, and M u is the average of the color differences between the three pairs of virtual fluorescent color samples under a simulator. It was reported that at least six light‐emitting diode (LED) channels with the full widths at half maximum (FWHM) of 30 nm are required to produce AA‐grade ( M v < 0.25, M u < 0.25) daylight simulators . Furthermore, it is possible to create D50, D55, D65, and D75 daylight simulators with AA‐grade using six LED channels with peak wavelengths (WLs) of 357, 420, 474, 533, 595, and 660 nm .…”
Section: The Optimized Peak Wls Of Channels For the Spectrally Tunablmentioning
confidence: 99%
“…2 Furthermore, it is possible to create D50, D55, D65, and D75 daylight simulators with AA-grade using six LED channels with peak wavelengths (WLs) of 357, 420, 474, 533, 595, and 660 nm. 2 However, we found that FWHMs of LEDs used in the six channels reported by Wei were 50 nm 2 , not 30 nm (which is an average value of AlInGaP and AlGaInN LEDs). Therefore, it is impossible to implement AA-grade daylight simulators with six LED channels.…”
mentioning
confidence: 99%
“…In [], the full width at half maximum (FWHM) value of 30 nm was wrongly reported. All the spectral simulations performed in the study were based on a FWHM of 50 nm.…”
mentioning
confidence: 99%